2017
DOI: 10.1186/s13550-017-0340-x
|View full text |Cite
|
Sign up to set email alerts
|

TSPO imaging using the novel PET ligand [18F]GE-180: quantification approaches in patients with multiple sclerosis

Abstract: BackgroundPET ligands targeting the translocator protein (TSPO) represent promising tools to visualise neuroinflammation. Here, we analysed parameters obtained in dynamic and static PET images using the novel TSPO ligand [18F]GE-180 in patients with relapsing remitting multiple sclerosis (RRMS) and an approach for semi-quantitative assessment of this disease in clinical routine.Seventeen dynamic [18F]GE-180 PET scans of RRMS patients were evaluated (90 min). A pseudo-reference region (PRR) was defined after id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 43 publications
3
45
2
2
Order By: Relevance
“…We also performed gadolinium contrast-enhancing MRI in the cohort of participants scanned with [ 18 F]GE-180 and observed no contrast enhancement (in lesion areas or otherwise), suggesting no extensive BBB breakdown. Although this observation does not exclude the possibility of micro-BBB breakdown, which could allow passage of [ 18 F]GE-180 molecules, but not the larger gadolinium molecules, through the disrupted area, the finding does concur with that of Vomacka et al [25]. The authors of this study also comment that (in their previous study [23]) areas with contrast enhancement in MR did not always correlate with increased [ 18 F]GE-180 signal, indicating that signal increases in PET are likely to be related to TSPO expression rather than exclusively BBB breakdown.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We also performed gadolinium contrast-enhancing MRI in the cohort of participants scanned with [ 18 F]GE-180 and observed no contrast enhancement (in lesion areas or otherwise), suggesting no extensive BBB breakdown. Although this observation does not exclude the possibility of micro-BBB breakdown, which could allow passage of [ 18 F]GE-180 molecules, but not the larger gadolinium molecules, through the disrupted area, the finding does concur with that of Vomacka et al [25]. The authors of this study also comment that (in their previous study [23]) areas with contrast enhancement in MR did not always correlate with increased [ 18 F]GE-180 signal, indicating that signal increases in PET are likely to be related to TSPO expression rather than exclusively BBB breakdown.…”
Section: Discussionsupporting
confidence: 54%
“…Participants had radial artery cannulation and blood was withdrawn continuously at a target rate of 2.5 ml min −1 from the start of each scan for the first 15 min. In addition, discrete blood samples were drawn at 0, 5, 10, 15, 30, 50, 70 and 90 min ([ 18 F]GE-180) or 0, 5,10,15,20,25,30,40,50,60,70,80 and 90 min ([ 11 C]PBR28) for metabolite analysis. For [ 18 F]GE-180, tracer concentrations in whole blood and plasma were measured in a well counter and radiometabolite analysis performed using two high performance liquid chromatography (HPLC) systems (Agilent 1260 Infinity and Agilent 110 Series) in isocratic mode.…”
Section: Arterial Plasma Measurementmentioning
confidence: 99%
“…The recently introduced TSPO ligand GE-180 labeled with [ 18 F] offers an increased binding specificity and was tested in patients with gliomas [113] and neuroinflammatory diseases such as multiple sclerosis [114][115][116]. Regarding the delineation of glioma extent, it has been demonstrated that the [ 18 F]GE-180 uptake volume is significantly larger than the volume of contrast enhancement [113,117].…”
Section: Pet Imaging Of the Mitochondrial Translocator Proteinmentioning
confidence: 99%
“…One of the most interesting application is in patients with multiple sclerosis in which 18 F-GE180 already proved to be useful in the semi-quantitative assessment of neuroinflammation. In their work, Vomacka et al performed dynamic 18 F-GE180 PET scan (about 90 min) on 17 patients with relapsing remitting multiple sclerosis and subsequent static images in order to obtain SUV ratios that exhibited high values (ranging from 1.3 to 3.2) compared to frontal cortex, which was chosen as a pseudo-reference region as the least disease-affected brain area [75]. The duration of dynamic acquisition was based on the first human PET study on 18 F-GE180 that dates back to 2016, in which the authors evaluated after a 210-min acquisition on 10 healthy patients, five different kinetic models and concluded that the best represented brain 18 F-GE180 kinetics across regions was the reversible two-tissue compartment model (2TCM4k).…”
Section: Future Perspectivesmentioning
confidence: 99%